Mapping the Research Landscape of Green Marketing, Brand Trust, and Purchase Decision: A Bibliometric Analysis and Systematic Review on Database Scopus - Purwanitasari, Lili; Soetjipto, Budi Eko; Wardhana, Ludi Wishnu (PT. Maju Malaqbi Makkarana, 2025)
This study aims to map the research landscape on green marketing, brand trust, and purchase decisions using a bibliometric approach and systematic review using the Scopus database. This study identifies research trends, scholarly contributions, and gaps in the literature. Using VOSviewer software, this study processed data from 61 articles published between 2019-2024. The analysis results show that most articles with the theme of green marketing brand trust and purchase decision were published in 2023 (14 documents), while the most published journal was the Journal of Retailing and Consumer Services. The most journal affiliations are from Harbin Institute of Technology (3 documents), the most journals published from Indonesia are 18 documents, the most subjects are Business, Management, and Accounting areas with a percentage of 46.2%, keywords related to themes include purchase intention, product quality, consumer behavior, marketing, brand image, sales, green brand trust, e-commerce.